Joint channel and impulsive noise estimation method for MIMO-OFDM systems - Xinrong LYU; Youming LI; Qiang GUO (Tongxin xuebao)
Aiming at the impulsive noise occurring in MIMO-OFDM systems， a joint channel and impulsive noise estimation method based on the multiple measurement vector compressed sensing theory was proposed.The channel impulse response and the impulsive noise were combined to form a row sparse matrix to be estimated， and a multiple measurement vector compressed sensing model based on all subcarriers was constructed.As the measurement matrix was partially unknown due to the presence of unknown transmitted symbols in data tones， the multiple response sparse Bayesian learning theory and expectation maximization framework were adopted to jointly estimate the channel impulse response， the impulsive noise， and the data symbols which were regarded as unknown parameters.Compared with the existing methods， the proposed method not only utilizes all subcarriers but also does not use any a priori information of the channel and impulsive noise.The simulation results show that the proposed method achieves significant improvement on the channel estimation and bit error rate performance.